Aligning university library practices with the United Nations Sustainable Development Goals: A case study - Somaratna, Sajeewanie D.; Lankathilake, M.A. (University of Colombo, 2025)
Today, academic libraries have progressively developed beyond their traditional roles to become vital enablers of sustainability, equity, and innovation within higher education institutions. Over the past decade, many scholars have aimed to align library practices with the United Nations Sustainable Development Goals (SDGs). However, in the Sri Lankan context, studies focusing on the SDGs in libraries are scattered and abstract. Therefore, this study aims to explore and map the sustainable library practices of the Science Faculty Library at the University of Colombo to the SDGs. This library operates as an academic blended library and was awarded the Green Building Certification in 2021. It serves approximately 4,000 students enrolled in the Faculty of Science, of whom 54% are female. Using a qualitative research approach, data were collected through document analysis, service audits, and direct observations. The mapping of library practices against the SDGs shows that they are directly or indirectly aligned with all 17 SDGs. The direct contributions include 13 goals, such as no poverty (SDG 1), good health and well-being (SDG 3), quality education (SDG 4), gender equality (SDG 5), clean water and sanitation (SDG 6), clean energy (SDG 7), decent work and economic growth (SDG 8), industry, innovation, and infrastructure (SDG 9), reduced inequalities (SDG 10), sustainable cities and communities (SDG 11), responsible consumption (SDG 12), climate action (SDG 13), and partnerships for the goals (SDG 17). Findings highlight the library’s multifaceted impact, ranging from providing inclusive access to information to promoting mental well-being, sustainable infrastructure, and ethical academic practices. Notably, the library's certified green building design, utilisation of solar energy, and digital platforms support broader environmental and innovation objectives. Additionally, career guidance programmes and outreach activities address employability and lifelong learning. This research also demonstrates that academic libraries can serve as operational models of sustainability, effectively bridging educational missions with global development agendas. Furthermore, the study recommends incorporating SDG-aligned indicators into library strategic plans and expanding collaborative partnerships to enhance impact.
Keywords: Sustainable Development Goals; SDGs; University libraries